Should government smooth exchange rate risk? - Ilan Goldfajn; Marcos Antonio Silveira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
A general equilibrium model is built to explain if there are circumstances in which exchange rate risk smoothing (ERRS) policies may bring a Pareto-improvement for a indebted small open (home) economy. The model shows that this is the case when overpessimistic foreign creditors demand a large spread on the default risk-free world interest rate, whose size can be reduced by ERRS policies and, in addition, market imperfections, such as information asymmetry between foreign investors and domestic debtors, prevent home economy's residents from internalizing all benefits and costs of the exchange rate risk reallocation into their allocative decisions.
Keywords: 330; Währungsrisiko; Kleine offene Volkswirtschaft; Wechselkurspolitik; Theorie